Early childhood caries trends and surveillance shortcomings in the Czech Republic - Lenčová Erika; Pikhart Hynek; Broukal Zdeněk (BMC, 2012)
Abstract Background Despite the decline in childhood caries prevalence, seen particularly in 1980s, in recent years there have been reports that the declining trend has stopped or even reversed in some countries. The aim of the study was to analyse data from previous epidemiological studies on early childhood caries in the Czech Republic, conduct a secondary analysis of trend in dental caries prevalence, and discuss issues related to national oral health surveillance. Methods Since the 1990s, caries prevalence in preschool children was monitored by two independent bodies: Institute of Health Information and Statistics (IHIS) that conducted 5 cross-sectional surveys over the period 1994-2006, and Institute of Dental Research (IDR) that conducted 4 studies over the years 1998-2010. Both study series differed in methods of sample selection and approaches to examiner training. For the assessment of the caries prevalence trends, regression modelling was used for the following oral-health indicators: caries experience, mean number of teeth with untreated caries (dt) and percentage of caries-free children. Results In both study series, a significant overall trend of declining caries experience and level of untreated caries, and an increasing trend of percentage of caries-free children was observed (p < 0.05). In IHIS studies, caries experience reduced from 3.5 to 2.7; dt reduced from 2.2 to 1.5 and a proportion of caries-free children increased from 23.9 to 42.2%. In IDR studies, caries experience reduced from 3.7 to 2.98; dt reduced from 2.5 to 2.1 and a proportion of caries-free children increased from 26.7 to 44.9%. Conclusions Both study series identified a significant decline of caries prevalence particularly in the 1990s and early 2000s. By the end of the investigated period, flattening of the caries decline was observed. The positive trend was observed in the absence of any systematic preventive initiatives on a population level. With respect to the above the authors assume that in the Czech Republic there still is a potential for further caries reduction in preschool population. This, however, cannot be expected without any health policy interventions. Oral health surveillance in the Czech Republic should be promoted by competent regulatory authorities.